Befriending the Religious Other: The Possibility and Blessing of Interreligious Friendship. - Jaiyesimi, Wemimo B. (Journal of Ecumenical Studies)
Taking seriously the challenge posed by religious difference to interreligious friendship, this essay argues for the possibility of this form of friendship from a Christian theological viewpoint. In arguing for interreligious friendship's possibility, the essay goes against accounts of friendship, such as that influentially articulated by Aristotle, wherein friendship's possibility is predicated on the would-be friends' sharing agreement. Instead of this, drawing on Janet Soskice's theological anthropology of friendship, it argues that friendship with the religious other is possible given that the reality of our ontological distance from the divine Godhead does not close off divine-human friendship. Finally, it suggests that this form of friendship offers important sources of spiritual and moral nourishment.